Construct validity of the First-Year Inventory (FYI Version 2.0) in 12-month-olds at high-risk for Autism Spectrum Disorder. (January 2021) - Lee, Helen Y; Vigen, Cheryl; Zwaigenbaum, Lonnie; Smith, Isabel M; Brian, Jessica; Watson, Linda R.; Crais, Elizabeth R.; Baranek, Grace T
This study examines the construct validity of the First-Year Inventory 2.0 with respect to other established instruments in a sample of high-risk infant siblings of children with Autism Spectrum Disorder. The First-Year Inventory 2.0 is a parent-report screening instrument designed to identify 12-month-old infants at risk for an eventual diagnosis of Autism Spectrum Disorder and consists of two domains: Social-Communication and Sensory-Regulatory. Although the First-Year Inventory 2.0's screening psychometrics have been examined, its construct validity has not been investigated. In a sample of 112 high-risk 12-month-olds, we examined the First-Year Inventory 2.0's associations with the Autism Observation Scale for Infants, an observer-based Autism Spectrum Disorder screener, and with other developmental instruments measuring similar areas in social communication and regulatory functioning in young children. Findings generally supported the First-Year Inventory 2.0 associations with other instruments in expected ways. The First-Year Inventory 2.0 Social-Communication domain was notably associated with the Autism Observation Scale for Infant's total score and with language and communication domains of the Vineland and the Mullen. The Sensory-Regulatory domain showed minimal associations with other instruments that only had a few sensory items. Considering different objectives and strengths of assessments, researchers and clinicians are encouraged to utilize a variety of instruments in a comprehensive evaluation of a child. Lay abstract: The First-Year Inventory 2.0 is a parent-report screening instrument designed to identify 12-month-old infants at risk for an eventual diagnosis of Autism Spectrum Disorder. This instrument focuses on Social-Communication and Sensory-Regulatory areas of infant behavior. Although the First-Year Inventory 2.0 screening performance has been previously studied, its validity has not been examined. Establishing validity of an instrument is important because it supports the effectiveness and the reliability of the instrument. In this study, we examined relationship between the First-Year Inventory 2.0 (Social-Communication and Sensory-Regulatory areas) and other instruments that measure similar areas of infant behavior in a sample of high-risk infant siblings of children with Autism Spectrum Disorder. These other instruments share some common aims and theoretical areas with the First-Year Inventory 2.0: the Autism Observation Scale for Infants, the Mullen Scales of Early Learning, the Vineland Adaptive Behavior Scales-II, and the Infant Behavior Questionnaire. Findings generally supported the validity of the First-Year Inventory 2.0 with other instruments. In particular, the Social-Communication area of the First-Year Inventory 2.0 showed greater commonality with other instruments than in the Sensory-Regulatory area. The Sensory-Regulatory area seemed to be a unique feature of the First-Year Inventory 2.0 instrument. Considering different aims and strengths of assessments, researchers and clinicians are encouraged to utilize a variety of instruments in a comprehensive evaluation of a child.